Provitamin A accumulation in Cassava (Manihot esculenta) roots driven by a single nucleotide polymorphism in a phytoene synthase gene[W] - Welsch, R; Arango, Jacobo; Bar, C; Salazar, B.; Al-Babili, S.; Beltrán Giraldo, Jorge Alonso; Chavarriaga Aguirre, Paul; Ceballos, H.; Tohme, Joseph M.; Beyer, Peter (Oxford University Press, 2010)
Cassava (Manihot esculenta) is an important staple crop, especially in the arid tropics. Because roots of commercial cassava cultivars contain a limited amount of provitamin A carotenoids, both conventional breeding and genetic modification are being applied to increase their production and accumulation to fight vitamin A deficiency disorders. We show here that an allelic polymorphism in one of the two expressed phytoene synthase (PSY) genes is capable of enhancing the flux of carbon through carotenogenesis, thus leading to the accumulation of colored provitamin A carotenoids in storage roots. A single nucleotide polymorphism present only in yellow-rooted cultivars cosegregates with colored roots in a breeding pedigree. The resulting amino acid exchange in a highly conserved region of PSY provides increased catalytic activity in vitro and is able to increase carotenoid production in recombinant yeast and Escherichia coli cells. Consequently, cassava plants overexpressing a PSY transgene produce yellow-fleshed, high-carotenoid roots. This newly characterized PSY allele provides means to improve cassava provitamin A content in cassava roots through both breeding and genetic modification.